Recurrent skull vault actinomycosis: A case report and review of literature - Abdur Rehman Mohamad (17280583) (2021)
Actinomycosis is an uncommon cause of central nervous system infection. A case of skull bone osteomyelitis with epidural empyema is presented. A 44-year-old man presented with chronic osteomyelitis of skull vault with epidural and subgaleal collection diagnosed by histopathology as actinomycosis. He had similar lesion at the same site 10 years ago, which was excised completely. Recurrent Actinomycosis of the skull vault is uncommon in literature. This case highlights the importance of considering actinomycosis as a differential diagnosis of tumorous growths and stresses on the importance of tissue histopathology for diagnosis and need for surgery to control the disease. Treatment is prolonged, therefore compliance with the long-term antibiotic duration is essential to prevent complications and avoid recurrence. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2021.e01215